Investigation on the possibility of determining plasma parameters by the method of low-frequency diagnostics - Kovtun, Yu.V.; Pinos, I.B.; Skibenko, A.I.; Skibenko, E.I. (Вопросы атомной науки и техники, 2014)
A possibility of determining some parameters (density, collision rate, magnetic field strength, mass-and-ion charge) of the plasma being in a magnetic field is under consideration. Peculiarities in the change of probing wave refraction and absorption values depending on the plasma parameters are investigated. Appreciation is made of the possibility for plasma diagnostics by means of probing using low-frequency electromagnetic waves with frequencies of ion-cyclotron range. Рассмотрена возможность определения некоторых параметров плазмы (плотности, частоты соударений, напряженности магнитного поля, массы и заряда ионов), находящейся в магнитном поле, за счет исследования особенностей изменения показателей преломления и поглощения зондирующей волны от этих параметров. Оценена возможность диагностики плазмы с помощью зондирования низкочастотными электромагнитными волнами с частотами порядка ионно-циклотронных. Розглянута можливість визначення деяких параметрів плазми (густини, частоти зіткнень, напруженості магнітного поля, маси і заряду іонів), що знаходиться в магнітному полі, за рахунок дослідження особливостей зміни показників заломлення і поглинання зондуючої хвилі від цих параметрів. Оцінена можливість діагностики плазми за допомогою зондування низькочастотними електромагнітними хвилями з частотами порядку іонно-циклотроних.